CREATIVE THINKING SKILLS IN SUB MATERIAL FACTOR AFFECTING THE RATE OF REACTION WITH THE APPLICATION OF ONLINE-BASED WORKSHEETS ON GUIDED INQUIRY - Mauludiah, cindy; Novita, Dian (JPPS (Jurnal Penelitian Pendidikan Sains), 2021)
One of the skills that must be possessed in the 21st century is the ability to think creatively. This study aims to apply student worksheets (LKPD) to improve creative thinking skills through guided inquiry learning models. The research method used a quantitative descriptive method where only one class was used without a comparison class with a one-group pretest-posttest research design. The instruments used were observation sheets of guided inquiry implementation, student activities, knowledge test sheets, creative thinking skills test sheets, and student response questionnaires. The research results obtained data: (1) The implementation of guided inquiry learning models at the first and second meetings went well with a percentage of 97.72% and 98.71%. (2) The percentage of relevant activities is higher than in irrelevant activities. (3) The learning outcomes of the knowledge test and the creative thinking skills test increased as evidenced by the N-gain value on the knowledge test of 0.79 with the high category and the creative thinking skills test of 0.77 with high criteria (4) The results of the response of students showed a response positive as evidenced by the results of the classical questionnaire percentage of 87.3% with the very good category. This shows that learning by applying guided inquiry-based LKPD is effective for improving students' creative thinking skills on the sub-material factors that affect the rate of reaction.